Equilibrium and kinetic studies on the adsorption of thiophene and benzothiophene onto NiCeY zeolites. Issue 37 (26th April 2017) - Fei, Liu; Rui, Jingwei; Wang, Rijie; Lu, Yanfei; Yang, Xiaoxia
Abstract : NiCeY zeolites were prepared by ion-exchanging NaY with 0.1 M Ni(NO3 )2 and 0.1 M Ce(NO3 )3 solution. Abstract : NiCeY zeolites were prepared by ion-exchanging NaY with 0.1 M Ni(NO3 )2 and 0.1 M Ce(NO3 )3 solution. The experiment for the adsorption of thiophene and benzothiophene from a model fuel has been carried out by using the prepared NiCeY. The adsorption isotherms and kinetics of thiophene and benzothiophene in n -octane have been studied, and the parameters (Δ H, Δ G, Δ S ) for the adsorption were calculated. The effect of adsorption temperature and contact time on the adsorption were investigated through the static method at ambient pressure. The experimental data was analyzed using the pseudo first order and pseudo second order kinetic equations and Langmuir and Freundlich models. The results show that the isotherm equilibrium for thiophene and benzothiophene adsorption can be represented by the Langmuir equation.